The role of the audiencein the Turkish film industry - PELTEKOĞLU, ZEYNEP FİLİZ (My University, 2022)
According to consumer-centered marketing theories, “the consumer is the king”. As there are so many alternative brands in the market, it is vital to understand the reasons for customers’ choices. Likewise, in the film industry, the audience is “king” heaps of times. The filmmakers rely on popular genres, characters, actors, and directors to gain the target audience’s appreciation. However, when it comes to art, cultural and creative industries, implementing customer-focused strategies has caused controversy. If cinema is an art, how important should the expectations and needs of the audience be? This study addresses the audience’s role in the Turkish film industry. Following a literature review of the Turkish film industry’s history and current structure, the study interprets the audience profile and box office data using statistical analysis. The study shows that the audience has been influential in almost every period of the Turkish film industry and at every stage of the value chain, from planning to distribution